Chair-Making For Beginners - Illustrated by Some Episodes in the Career of John Thomson (1765-1846) (Res Medica, 2014)
John Thomson is arguably one of the most interesting characters to have been associated with the Royal Medical Society. His interests were wide ranging; from military surgery and the treatment of venereal disease (two areas often closely connected in those times) to chemistry and the newly emerging specialty of pathology. It is, however, with his interest in medical education and his ability to persuade those in authority to create professorial chairs for himself to occupy that I shall deal in this article.